(3GdEMUGA (B/s - (3adjad, cGeds; (3MeOGf, aJMjs ((3YeGf(B: s (3OGQ GdefGgL ddfTQ hGdJhRjY(B, s, 2012)
(3LeY GdHjGfGJ hJHhjHgG(B- (3ebGjjS GdfRYI GdeQcRjI(B- (3ebGjjS GdJTJJ(B- (3GdEQJHGW hGdGfMOGQ(B- (3fXQjI GdEMJeGdGJ(B- (3GdJhRjYGJ GdEMJeGdjI(B- (3GdJbOjQ hENJHGQ GdaQVjGJ(B- (3GdCQbGe GdbjGSjI(B- (3GdSdGSd GdRefjIs
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEMUGA GdESJOdGdjs; (3GdEMUGA GdhUajs